Cardiac Imaging by Nuclear Magnetic Resonance - Burdine, John A. (1983)
Proton nuclear magnetic resonance (NMR) imaging has been developed and improved over the past few years to the state that images of static structures have recently shown spatial resolution equivalent or superior to other techniques such as X rays, ultrasound, or gamma ray-emitting radionuclides. The current state of NMR development is described; however, use of this exciting new diagnostic modality depends on the results of extensive clinical trials.